Find the Center

Find the Radius

Write the Equation

Change Forms

100

(x-2)^{2 }+ (y-5) = 9^{2}, the center point is ...

(2, 5)

100

(y-3)^{2 }+ (x-1)^{2} = 9, the radius of the circle is ...

3

100

The center is (1, -3) and the radius is 2

(x-1)^{2 }+ (y+3)^{2 }= 4

100

Change to general form:
(x + 9)^{2} + (y - 2)^{2} = 64

x^{2} +y^{2} + 18x - 4y + 21 = 0

200

(x-3)^{2 }+ (y-4)^{2 }= 25^{2}, the center point is ...

(3, 4)

200

(y-5)^{2 }+ (x-14)^{2} = 16, the radius of the circle is ...

4

200

The center is (2, -1) and the radius is 4

(x-2)^{2 }+ (y+1)^{2 }= 16

200

Change to general form: (x - 10)^{2} + (y -12)^{2} = 36

x^{2} + y^{2} - 20x - 24y + 208 = 0

300

(x-1)^{2} + (y-2)^{2} = 3^{2}, the center point of the circle is ...

(1, 2)

300

(y-1)^{2 }+ (x-5)^{2} = 25, the radius of the circle is ...

5

300

The center is (1, -4) and the radius is 3

(x-1)^{2 }+ (y+4)^{2 }= 9

300

Change to general form: (x + 16)^{2} + (y + 7)^{2} = 1

x^{2} + y^{2} + 32x + 14y + 304 = 0

400

(x-2)^{2 }+ (y+5)^{2 }= 17^{2}, the center point is ...

(2, -5)

400

(y+7)^{2 }+ (x +5)^{2} = 49, the radius of the circle is ...

7

400

The center is (0, 3) and the radius is √14

x^{2 }+ (y-3)^{2 }= 14

400

Change to standard form: x^{2} + y^{2} - 10x + 2y + 10 = 0

(x - 5)^{2 }+ (y + 1)^{2} = 16

500

(x+8)^{2 }+ (y+17)^{2 }= 49^{2}, the center point of the circle is ...

(-8, -17)

500

x^{2 }+ (y − 3)^{2 }= 14, the radius of the circle is ...

√14

500

The center is (13, -13) and the radius is 4

(x − 13)^{2 }+ (y + 13)^{2 }= 16

500

Change to standard form:

x^{2} + y^{2} - 32x + 10y + 280 = 0

(x - 16)^{2} + (y + 5)^{2} = 1